2021
DOI: 10.1002/jsfa.11391
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heterocyclic amines in braised sauce beef and the effects of different cooking conditions on the formation of heterocyclic amines

Abstract: BACKGROUND Cooked meat is a good source of high‐quality protein. However, during long‐term cooking of meat, radical‐induced lipid and protein oxidation may lead to the formation of poisonous compounds, such as heterocyclic amines (HAs). This work investigated a testing method for HAs and it describes that cooking temperature, cooking time and repeated cooking times have influences on the overall quality of braised sauce beef and the effect of HAs formation. RESULTS The improved method has a good separation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…R 2 values were above 0.99 which indicated good linearity. Recovery rates, RSD, LOD, and LOQ of HAAs were coherent with previous reports and demonstrated high recovery and sensitivity of the method (Oz et al, 2016;Yan et al, 2021;Zhou et al, 2022).…”
Section: Quantitative Analysis Of Haassupporting
confidence: 89%
“…R 2 values were above 0.99 which indicated good linearity. Recovery rates, RSD, LOD, and LOQ of HAAs were coherent with previous reports and demonstrated high recovery and sensitivity of the method (Oz et al, 2016;Yan et al, 2021;Zhou et al, 2022).…”
Section: Quantitative Analysis Of Haassupporting
confidence: 89%
“…HAs are generated by interactions of precursors such as creatine, creatinine, hexose, and amino acids during high-temperature processing in protein-rich food materials. , Long-term animal studies have confirmed that HAs are a large class of carcinogenic and mutagenic compounds, and the frequent consumption of heat-processed foodstuffs containing HAs will enhance the risk of human cancer such as gastric and colon cancers. , Furthermore, HAs can be divided into aminoimidazoazoarenes (AIAs) and amino carbolines (ACs) based on their formation pathways and structures . AIAs are universally considered to be formed by HA precursors such as sugars, creatinine, and amino acids when cooking between 150 and 300 °C, which are known as imidazoquinoline-type (IQ-type) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Furthermore, HAs can be divided into aminoimidazoazoarenes (AIAs) and amino carbolines (ACs) based on their formation pathways and structures. 15 AIAs are universally considered to be formed by HA precursors such as sugars, creatinine, and amino acids when cooking between 150 and 300 °C, which are known as imidazoquinoline-type (IQtype) compounds. Nevertheless, ACs are generated by protein pyrolysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liao studied the kinetics of the formation of HAAs in the model system and found that norharman and harman have lower activation energy than other polar HAAs, which meant that β‐carboline heterocyclic amines are less sensitive to temperature and are easy to form at low temperature (Liao, 2008). Zhou et al detected two kinds of HAAs (norharman and harman) in the braised sauce beef and found that the content gradually increased and then stabilized as the cooking temperature increased (Zhou et al, 2021). Shen cooked the braised pork at 100℃ and found that the contents of norharman and harman in braised pork were 84.99 and 140.21 ng/g, respectively (Shen et al, 2018).…”
Section: Resultsmentioning
confidence: 99%